2016
DOI: 10.3762/bjoc.12.261
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between cyclodextrins and cellular components: Towards greener medical applications?

Abstract: In the field of host–guest chemistry, some of the most widely used hosts are probably cyclodextrins (CDs). As CDs are able to increase the water solubility of numerous drugs by inclusion into their hydrophobic cavity, they have been widespread used to develop numerous pharmaceutical formulations. Nevertheless, CDs are also able to interact with endogenous substances that originate from an organism, tissue or cell. These interactions can be useful for a vast array of topics including cholesterol manipulation, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 158 publications
(177 reference statements)
2
48
1
Order By: Relevance
“…Hydroxypropyl-β-cyclodextrin was used as a vaccine adjuvant providing protection against the H1N1 influenza virus in the cynomolgus monkey model [52,53]. One point to emphasize is that for natural CDs, the intramolecular hydrogen bond with the CD molecule decreases their hydrogen bond formation with the surrounding water molecules [54]. This could lead to a potential negative antiviral action against the coronavirus.…”
Section: Cyclodextrinsmentioning
confidence: 99%
“…Hydroxypropyl-β-cyclodextrin was used as a vaccine adjuvant providing protection against the H1N1 influenza virus in the cynomolgus monkey model [52,53]. One point to emphasize is that for natural CDs, the intramolecular hydrogen bond with the CD molecule decreases their hydrogen bond formation with the surrounding water molecules [54]. This could lead to a potential negative antiviral action against the coronavirus.…”
Section: Cyclodextrinsmentioning
confidence: 99%
“…Cyclodextrins (CDs) are archetypal host molecules composed of glucose residues, typically 6, 7, or 8, linked in a ring creating truncated cone shapes with hydrophobic cavities . Consequently, they are able to encapsulate various hydrophobic guests . For instance, it was reported that water/oil/CD ternary mixtures are able to produce organic colloidal NPs .…”
Section: Figurementioning
confidence: 99%
“…[6] Consequently,t hey are able to encapsulate various hydrophobic guests. [6,7] For instance, it was reported that water/oil/CD ternary mixtures are able to produce organic colloidalN Ps. [8] In these systems, host-guest interactions between CDs and oil molecules ("hydrophilic" and "hydrophobic" tectons) lead to the formation of inclusion complexes( ICs) which spontaneously form CD NPs.…”
mentioning
confidence: 99%
“…In addition, it is interesting to note that, Cagno has even reviewed cyclodextrin"s "potential as active pharmaceutical ingredients (APIs) for the treatment of several illnesses." The quantity of cyclodextrins in a final drug formulation should be reduced because of its toxicity, cost, and dosage, and it is attained by the choice of a best suited cyclodextrin type, with optimized complexation technique to prepare formulation 3 . Therefore, this study was directed to illuminate solubility enhancement of the poorly soluble drug, Cefixime by complexing agent i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this study was directed to illuminate solubility enhancement of the poorly soluble drug, Cefixime by complexing agent i.e. 2-hydroxy)propyl-β-cyclodextrin (HPBCD), having good aqueous solubility with low toxicity profile 3 Cefixime-cyclodextrin complexes were prepared by spray drying method, and their properties were compared with those prepared by solvent evaporation, co-grinding, microwave irradiation, freeze drying and physical mixing. Cefixime is undergoing clinical trials for several diseases like gonorrhea, Diarrhea, Mucopurulent cervicitis (MPC), Pyelonephritis, Urinary Tract Infections, Typhoid Fever, Chronic Kidney Disease, Osteomyelitis 4,5 .…”
Section: Introductionmentioning
confidence: 99%